Obesity Risk Screening, Vision Complaints, Hearing based on Age and Waist Circumference - Sahrir Sillehu; Maryam Lihi (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
The aim of the study was to assess the relationship between age and obesity, to assess waist circumference and obesity. This type of quantitative research uses a cross-sectional design. The sample is 161 respondents. Data was collected using a questionnaire and measuring body mass index. Data were analyzed using the Pearson correlation test and linear regression analysis. The results showed that there were 144 respondents (89.4%) in the 18 - 25 year age category, 13 respondents (8.1%) for Body Mass Index for the first obesity category, 12 respondents (7.5%) for obesity II. There is a relationship between age and waist circumference with a p-value of 0.0001, there is a relationship between age and body mass index with a p-value of 0.0001. There is a relationship between age and body weight with a p-value of 0.001. Age is a risk factor for waist circumference, BMI, weight and hearing. As you get older, your waist circumference increases, your BMI increases, your weight increases and your age decreases your hearing ability. An obesity risk factor is age